Hydration and athletic performance the effect of dehydration on muscular strength - Catindig, Patricia Mae S. 2001-
Strength and conditioning have been widely used by athletes, and with the increasing popularity of its benefits, more people are now engaged in resistance training. It is often overlooked that it is a high-intensity exercise that demands more water, as this can affect training volume and the ability to lift weights. The purpose of this study was to investigate the effects of different hydration states (euhydrated and hypohydrated by 2-3% of body mass) on resistance training. Ten participants (mean age of 21.9 ± 1.44 years old) with resistance training experience (mean of 3.8 ± 1.6 months) were selected and participated in both hydration states. All participants underwent baseline testing for the euhydrated body mass and urine-specific gravity. On both testing sessions, the urine-specific gravity and body mass were measured before exercising. A maximum repetition test at 75% of the participant’s one-repetition maximum was used to determine muscle strength by performing 12-15 repetitions of back squats and bench presses for 3 sets. Results showed that there was a decrease in repetitions for back squat (p = 0.011) and bench press (p = 0.041) at two different hydration states. Thirst perception was found to have a significant difference between pre and post exercise (p = 0.01) for both exercises at two different hydration state. Higher temperatures (35.71°C ± 1.376) were also observed to have an effect on muscle strength performance when performing resistance training. The outcomes imply that hypohydration is likely to be associated with decrements in muscular strength and anaerobic performance